HUBUNGAN USIA DAN LAMA KERJA DENGAN RISIKO KELUHAN NYERI PUNGGUNG BAWAH PADA PEMBUAT EMPING TELO DI RINGINHARJO BANTUL DIY TAHUN 2017 - Dyah Wydiarti; Sri Sularsih Endartiwi (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2018)
Background: One aspect of occupational health is occupational disease, it is a worker risk due to industrial development and labor increase. According to Minister of Manpower and Transmigration Regulation no. Per.01 / MEN / 1981, occupational diseases are caused by a number of factors but some are from work, and lifestyle diseases. The problem that happened in Ringinharjo Village Hamlet from observation on September 26, 2017, obtained 10 respondents who are whole is teling emping maker, got result 80% of respondents have complaints of pain in back area, wrist and shoulder.  Objective: This study aims to determine the correlation between age and duration of work with risk of low back pain complaints on cassava emping maker in Ringinharjo, Bantul, DIY.  Methods: This research design is analytic survey study with cross sectional approach. A sample of 30 female teling employs was selected from the total sample. Data were analyzed by Kendall-tau test.  Result: There is correlation between age  = 0.000, duration of work  = 0.037 with lower back pain complaints.  Conclusion: There is a correlation between age and duration of work, with lower back complaints on cassava maker in Ringinharjo Village, Bantul District, Bantul Regency, DIY.